“PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2023-2025” - Dianawati; Diah Nurdiwaty; Mar’atus Solikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of financial performance as an indicator of the success of tourism sector companies in maintaining business sustainability amid dynamic economic conditions and increasingly intense business competition. Previous studies have shown inconsistent results regarding the effect of liquidity, solvency, and profitability on financial performance, indicating the need for further research in the tourism sector, which remains relatively underexplored. This study aims to analyze the effect of liquidity proxied by Current Ratio (CR), solvency proxied by Debt to Assets Ratio (DAR), and profitability proxied by Net Profit Margin (NPM) on financial performance measured using Return on Assets (ROA) in tourism sector companies listed on the Indonesia Stock Exchange (IDX). This study employed a causal research design with a quantitative approach. The data used were secondary data obtained from the financial statements of tourism sector companies listed on the Indonesia Stock Exchange for the 2023–2025 period. The research sample consisted of 60 observations selected using purposive sampling. Data analysis techniques included classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination testing. The results indicate that solvency and profitability have a significant effect on financial performance, while liquidity has no significant effect on financial performance. In addition, liquidity, solvency, and profitability simultaneously have a significant effect on financial performance. These findings indicate that managing capital structure and improving the ability to generate profit are more dominant factors in enhancing the financial performance of tourism sector companies compared to the ability to fulfill short-term obligations.